Optoelectronic and solar cell applications of Janus monolayers and their van der Waals heterostructures. Issue 34 (15th August 2019) - Idrees, M.; Din, H. U.; Ali, R.; Rehman, G.; Hussain, T.; Nguyen, C. V.; Ahmad, Iftikhar; Amin, B.
Abstract : Janus monolayers and their van der Waals heterostuctures are investigated by hybrid density functional theory calculations. Abstract : Janus monolayers and their van der Waals heterostuctures are investigated by hybrid density functional theory calculations. MoSSe, WSSe, MoSeTe and WSeTe are found to be direct band gap semiconductors. External electric fields are used to transform indirect MoSTe and WSTe to direct band gap semiconductors. MoSSe–WSSe, MoSeTe–WSeTe and MoSTe–WSTe vdW heterostructures are also indirect band gap semiconductors with type-II band alignment. Similar to the corresponding monolayers, in some of the above mentioned vdW heterostructures an external electric field and tensile strain can transform indirect to direct band gaps, while sustaining type-II band alignment. Janus monolayers have lower values of the work function ( ϕ ) than their vdW heterostructure counterparts. Furthermore, absorption spectra, absorption efficiency, and valence(conduction) band edge potentials are calculated to understand the optical and photocatalytic behavior of these systems. Red and blue shifts are observed in the position of excitonic peaks due to the induced strain in Janus monolayers. Strong device absorption efficiencies (80–90%) are observed for the WSeTe, MoSTe and WSTe monolayers in the visible, infra-red and ultraviolet regions. Energetically favourable band edge positions in Janus monolayers make them suitable for water splitting at zero pH. We find that the MoSSe–WSSe heterostructure and the MoSTe monolayer are promising candidates for water splitting with conduction and valence band edges positioned just outside of the redox interval.